Aisyiyah Cadre Training About Cervical Cancer and Early Detection in The Gerakan Aisyiyah Sehat (GRASS) - Lidia Hastuti; Ayu Rizky; Yenni Lukita; Nuruniyah; Usman (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Background: Cancer cervix is a type of cancer that develops in the neck uterus and parts caused by infection with the Human Papilloma Virus (HPV) type of oncogenic. The incidence of cancer in the high cervix in Indonesia makes it so as one of the problems of health. Activity This aims to increase the knowledge cadre Aisyiyah about cancer cervix and early detection through training programs in 14 districts/cities in West Kalimantan. The method used is stage training with several stages that include stage preparation, implementation of online training via Zoom, and evaluation of program effectiveness. The results show that training succeeds increase the knowledge of participants with the average score of knowledge reaching 85.65±2.45 and the level of presence of participants by 95%. Training This shows success in increasing awareness and action preventive to cancer cervix in society. Success This opens opportunity for advanced programs to expand reach and impact positive to health women in the region.